Computation of Vertex-Based Topological Descriptors of Organometallic Monolayers of TM3C12S12. (21st October 2021) - Alrowaili, Dalal; Ashraf, Faraha; Ali, Rifaqat; Shoukat, Arsalan; Shaheen, Aqila; Azeem, Mehran; Siddique, Imran
Abstract : Topological descriptors are mathematical values related to chemical structures which are associated with different physicochemical properties. The use of topological descriptors has a great contribution in the field of quantitative structure-property relationship (QSPR) and quantitative structure-activity relationship (QSAR) modeling. These are mathematical relationships between different molecular properties or biological activity and some other physicochemical or structural properties. In this article, we calculate few vertex degree-based topological indices/descriptors of the organometallic monolayer structure. At present, the numerical programming of the biological structure with topological descriptors is increasing in consequence in invigorating science, bioinformatics, and pharmaceutics.